2010
DOI: 10.3109/15563650903585937
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram causes fewer seizures in human overdose than citalopram

Abstract: CONTEXT: Seizures are a recognized complication of acute overdose with the racemic (1:1 ratio of R-and S-enantiomers) selective serotonin reuptake inhibitor antidepressant citalopram. OBJEC-TIVE: We tested the hypothesis that escitalopram (the therapeutically active S-enantiomer of citalopram) causes fewer seizures in overdose than citalopram at comparable doses of the S-enantiomer. METHODS: Multicenter retrospective review of cases with citalopram and escitalopram overdose reported to German, Austrian, and Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
23
0
2
Order By: Relevance
“…In a multicenter retrospective review, escitalopram, the S-enantiomer of citalopram, was found to cause fewer seizures in overdose situations. 10 Metabolic acidosis has been reported in 4 cases of citalopram overdose including a case of seizures followed by metabolic acidosis in a 20-year-old woman after ingesting 1800 mg of citalopram in a suicide attempt. 11 Citalopram and escitalopram also have rarely been reported to cause QTc interval widening with therapeutic use and in overdose because of inhibition of sodium, potassium, and calcium channels.…”
Section: Citalopram/escitaloprammentioning
confidence: 98%
“…In a multicenter retrospective review, escitalopram, the S-enantiomer of citalopram, was found to cause fewer seizures in overdose situations. 10 Metabolic acidosis has been reported in 4 cases of citalopram overdose including a case of seizures followed by metabolic acidosis in a 20-year-old woman after ingesting 1800 mg of citalopram in a suicide attempt. 11 Citalopram and escitalopram also have rarely been reported to cause QTc interval widening with therapeutic use and in overdose because of inhibition of sodium, potassium, and calcium channels.…”
Section: Citalopram/escitaloprammentioning
confidence: 98%
“…Эсциталопрам метаболизируется через CYP2C, благодаря чему не обладает ни индукционным, ни ингибиторным профилем по отношению к противоэ-пилептической терапии [36].…”
Section: больная к-ва 1985 года рожденияunclassified
“…Both citalopram and escitalopram are capable of provoking generalized seizures 40,41. Citalopram and escitalopram are known to cause dose-dependent QT prolongation, although the mechanism remains uncertain and may be unrelated to serotonin reuptake per se 1,2.…”
Section: Pharmacological Mechanisms Responsible For Cardiovascular Efmentioning
confidence: 99%